The Conception of the Ultima Ratio Principle - Dambrauskienė, Aušra (Teisė, 2016)
[full article and abstract in Lithuanian; abstract in English] In the process of criminalisation of certain offences, the relevant requirements for legislature must be raised, which limit discretion of legislature and do not allow distorting the essence of criminal law. The theory of criminalisation determines these requirements and one of them is the ultima ratio (latin last, final argument, last resort) principle. This principle means that criminal liability, being the most restricting measure in terms of rights and freedoms of persons, must be applied in exceptional cases only, when other legal or non-legal means are not sufficient in order to stop criminality. The content of the ultima ratio principle includes: 1) serious violation of individual, social and state legal interests; 2) absence of alternative influence means for this violation in other legal branches. The content of the ultima ratio principle also encompasses inner (consistency of criminal law system) and outer (the means of criminal law is exceptional when compared with the means of other legal branches) aspects as well as aspects of legislature and implementation of law. The ultima ratio principle is given a different meaning: from the scientific recommendation for legislature to the obligatory constitutional principle. Due to the relation with the defence of fundamental rights and the principle of proportionality, which makes ultima ratio peremptory, the ultima ratio principle is considered as the regulatory provision of law – the legal principle which is related to criminal justice. Since the ultima ratio principle functions, first of all, in legislature, i.e. in the process of criminalization, it must be considered as the substantive special principle of criminal policy.